How is risk different in family and non-family businesses? A comparative statistical analysis during the COVID-19 pandemic. Issue 4 (26th November 2021) - Santos, Eulalia; Tavares, Vasco; Tavares, Fernando Oliveira; Ratten, Vanessa
Abstract : Purpose: Risk is part of corporate activity and a consequence of the businesses' demands, the market and the changes in companies and their surroundings. The way that risk is managed is different between family and non-family businesses. The paper aims to compare the different risk types experienced in the context of the coronavirus disease (COVID-19) pandemic among family and non-family businesses and to analyze whether operational, legal, strategic and image risks influence financial risks. Design/methodology/approach: The nature of the study is quantitative and based on a questionnaire survey that analyses the perception of risks by 1, 090 family businesses and 557 non-family businesses. Findings: The results show the existence of statistically significant differences in the perception of financial and legal risks between family and non-family businesses, where the former being the businesses that give more importance to these risks. The perception of operational, legal, strategic and image risks have a positive influence on the perception of financial risk in family and non-family businesses. Originality/value: The results obtained in the study are important because they allow an understanding about the differences in risk management between family and non-family businesses, which can lead to greater corporate sustainability and increased financial performance.